Levator ani muscle innervation: Anatomical study in human fetus. Issue 6 (4th November 2016) - Nyangoh Timoh, Krystel; Bessede, Thomas; Lebacle, Cedric; Zaitouna, Mazen; Martinovic, Jelena; Diallo, Djibril; Creze, Maud; Chevallier, Jean‐Marc; Darai, Emile; Benoît, Gérard; Moszkowicz, David
Abstract : Aims: To characterize the nature and function of the levator ani muscle innervation pathways and to perform a comprehensive three‐dimensional reconstruction of female pelvic innervation. Methods: A computer‐assisted anatomical dissection protocol was applied to seven female human fetuses, after approval from the national biomedicine agency. Specimens were serially sectioned and immunostained for overall (antibody against protein S100), somatic (antibody against peripheral myelin protein 22), adrenergic (antibody against tyrosine hydroxylase), cholinergic (antibody against vesicular acetylcholine transferase), and nitrergic (antibody against the neural isoform of nitric oxide synthase) nerve fibers. Slides were digitized for three‐dimensional reconstructions using WinSurf®. Results: Three main nerve pathways to the levator ani muscle were observed: the levator ani nerve, the pudendal nerve, and the inferior hypogastric plexus. The pudendal nerve was both somatic and autonomic, located below the levator ani muscle ( infralevator pathway ), supplying innervation to the inferior aspect of the levator ani muscle. The levator ani nerve was solely somatic, located above the levator ani muscle ( supralevator pathway ), supplying innervation to the superior aspect of the levator ani muscle. The inferior hypogastric plexus nerve fibers were solely autonomic, located in between the levator ani muscle and pelvic organs ( endolevator pathway ), supplying innervation to the medial portion of the levator ani muscle. Conclusions: Our study provides a new representation of levator ani muscle innervation with three nerve pathways, and the levator ani muscle itself as an anatomical landmark.